2004
DOI: 10.1128/jvi.78.4.1882-1892.2004
|View full text |Cite
|
Sign up to set email alerts
|

Reovirus Nonstructural Protein μNS Recruits Viral Core Surface Proteins and Entering Core Particles to Factory-Like Inclusions

Abstract: Mammalian reoviruses are thought to assemble and replicate within cytoplasmic, nonmembranous structures called viral factories. The viral nonstructural protein NS forms factory-like globular inclusions when expressed in the absence of other viral proteins and binds to the surfaces of the viral core particles in vitro. Given these previous observations, we hypothesized that one or more of the core surface proteins may be recruited to viral factories through specific associations with NS. We found that all three… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
145
0

Year Published

2007
2007
2021
2021

Publication Types

Select...
3
2
2

Relationship

1
6

Authors

Journals

citations
Cited by 96 publications
(149 citation statements)
references
References 57 publications
4
145
0
Order By: Relevance
“…A second possibility involves the poorly understood processes of genome packaging and genome replication, which in the Reoviridae occur within the viral inclusion bodies. The introduction of viral ssRNA into cells by transfection omits the presence of a core particle, which has been shown to be targeted to the viral inclusion bodies in the case of mammalian orthoreoviruses (2). It has been suggested that the core produces ssRNA within the inclusion body, thus supplying viral ssRNA for packaging and replication at the site of assembly of progeny cores.…”
Section: Discussionmentioning
confidence: 99%
“…A second possibility involves the poorly understood processes of genome packaging and genome replication, which in the Reoviridae occur within the viral inclusion bodies. The introduction of viral ssRNA into cells by transfection omits the presence of a core particle, which has been shown to be targeted to the viral inclusion bodies in the case of mammalian orthoreoviruses (2). It has been suggested that the core produces ssRNA within the inclusion body, thus supplying viral ssRNA for packaging and replication at the site of assembly of progeny cores.…”
Section: Discussionmentioning
confidence: 99%
“…Specific regions within the NS protein that are required for recruitment of the viral core and six other MRV proteins to VFs and for forming VFs have previously been identified (6,7,9,10,12) (Fig. 1A).…”
Section: Construction Of Plasmids Expressing the Tc Tag From Within Tmentioning
confidence: 98%
“…We separated the TC-NS mutants based on previously identified functions of NS to include the N-terminal third (aa 1 to 221), the central third (aa 222 to 470), and the C-terminal third (aa 471 to 721). Previous studies have found that the NS N-terminal third is both necessary and sufficient to bind virus proteins NS, 2, 1, 2, and 2, the C-terminal third is necessary and sufficient to bind 3, form VFs, and bind cellular clathrin, and the central third has been implicated in recruiting cellular protein Hsc70 to VFs (6,7,9,10,12,26,27). To examine the impact of the introduced TC-NS mutations, we cotransfected cells with each pTC-NS mutant or wild-type pT7-M3 along with plasmids expressing each of the other six virus proteins individually.…”
Section: Construction Of Plasmids Expressing the Tc Tag From Within Tmentioning
confidence: 99%
See 2 more Smart Citations